An analysis of Ethics Teaching Development in Education Curriculum of Thailand - Saithongdee, Krittaphars; Prabnok, Puttharak (Dhammathas Academic Journal, 2022)
Ethics is one of the important elements that states must include during circumstances, instruction in order for citizens to learn and understand ethics. The purpose of this article is to analyze the development of teaching ethics in Thai education curricula. The analytical study, it was found that the development of Thai ethical curricula can be divided into 6 periods although other ethical concepts were later incorporated but it is only to create harmony and link with Buddhist principles. It has also been found that ethical principles are applied in accordance with contemporary circumstances but we also found that the ethical teaching of Thai education courses only trains citizens to be ethical obedience. It is not yet a teaching to understand ethical principles.